Microglial Piezo1 mechanosensitive channel as a therapeutic target in Alzheimer’s disease - Ikiz, Erol D.; Hascup, Erin R.; Bae, Chilman; Hascup, Kevin N. (Frontiers in Cellular Neuroscience, 2024)
Microglia are the resident macrophages of the central nervous system (CNS) that control brain development, maintain neural environments, respond to injuries, and regulate neuroinflammation. Despite their significant impact on various physiological and pathological processes across mammalian biology, there remains a notable gap in our understanding of how microglia perceive and transmit mechanical signals in both normal and diseased states. Recent studies have revealed that microglia possess the ability to detect changes in the mechanical properties of their environment, such as alterations in stiffness or pressure. These changes may occur during development, aging, or in pathological conditions such as trauma or neurodegenerative diseases. This review will discuss microglial Piezo1 mechanosensitive channels as potential therapeutic targets for Alzheimer's disease (AD). The structure, function, and modulation of Piezo1 will be discussed, as well as its role in facilitating microglial clearance of misfolded amyloid-β (Aβ) proteins implicated in the pathology of AD.